2013
DOI: 10.2306/scienceasia1513-1874.2013.39.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of drought tolerance in transgenic cotton

Abstract: Tolerance against drought in T1 progeny of transgenic cotton (Gossypium hirsutum) previously transformed with GHSP26 (Heat Shock Protein Gene), GUSP1 (Universal Stress Protein Gene), and Phyto-B (Phytochrome-B Gene) was investigated at the vegetative, squaring, and boll formation stage. Detection of transgenes into the progeny plants through PCR showed a Mendelian inheritance pattern (3:1). Real-time PCR quantified the expression of GHSP26 as transgenic plants which tolerated drought stress for 10-12 days at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The performance of cotton lines over expressing stress responsive NAC1 (SNAC1) under drought and salt stress conditions was significantly better than WT plants in terms of boll number [36]. Similarly, cotton transgenic lines transformed with GHSP26 (Heat Shock Protein Gene), GUSP1 (Universal Stress Protein Gene) and Phyto-B (Phytochrome-B Gene) showed a significant increase in the number of bolls per plant, single boll weight, and seed cotton yield under drought stress, when compared with WT plants [34]. An improvement of yield components up to 24.0% in drought trials under field conditions was achieved using DREB1A-peanut plants across a wide range of stress intensities and resulted in higher harvest indices [62].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of cotton lines over expressing stress responsive NAC1 (SNAC1) under drought and salt stress conditions was significantly better than WT plants in terms of boll number [36]. Similarly, cotton transgenic lines transformed with GHSP26 (Heat Shock Protein Gene), GUSP1 (Universal Stress Protein Gene) and Phyto-B (Phytochrome-B Gene) showed a significant increase in the number of bolls per plant, single boll weight, and seed cotton yield under drought stress, when compared with WT plants [34]. An improvement of yield components up to 24.0% in drought trials under field conditions was achieved using DREB1A-peanut plants across a wide range of stress intensities and resulted in higher harvest indices [62].…”
Section: Discussionmentioning
confidence: 99%
“…Bellaloui et al [8] revealed that, under limited irrigation in the Mississippi Delta, the growth of cotton plants slowed to some extent, and this impacted the fiber and seed composition. More bolls were found in controlled environments than the stressed environments, and this indicated the negative effects of water stress on the number of bolls [90]. The flowering stage of cotton is found to be more sensitive to water stress than the vegetative one.…”
Section: Response Of Cotton Physiological Traits Yield and Yield Components To Irrigation Regimesmentioning
confidence: 91%
“…Hwang et al (2010) also supports the idea that the overexpression of NCED in some genotypes may promote greater tolerance to drought. For Shamim et al (2013) and Clément et al (2011), this can be explained, because the increase in NCED expression influences the synthesis of ABA, which in turn is related to stomatal closure. Other researchers have also reported the action of ABA on the stomatal closure of stressed plants, promoting greater tolerance to the limiting conditions of the water stress (Setter et al, 2011;Shatil-Cohen et al, 2011).…”
Section: Dmentioning
confidence: 99%